2015
DOI: 10.1111/sed.12190
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing 4000 years of mass movement and tsunami history in a deep peri‐Alpine lake (Lake Geneva, France‐Switzerland)

Abstract: The study of mass movements in lake sediments provides insights into past natural hazards at historic and prehistoric timescales. Sediments from the deep basin of Lake Geneva reveal a succession of six large-scale (volumes of 22 x 10^6 to 250 x 10^6 m^3) mass-transport deposits, associated with five mass movement events within 2600 years (4000 cal BP to 563 AD). The mass-transport deposits result from: (i) lateral slope failures (mass-transport deposit B at 3895 ± 225 cal BP and mass-transport deposits A and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 45 publications
1
56
1
Order By: Relevance
“…Known turbidite thickness in East Lake (millimeter scale) and the runoff of the river which attains peaks of 1–2 m 3 /s during snowmelt (peak discharge) also suggest that the hyperpycnal flows are rather dilute. These low‐energy hyperpycnal flows are not erosive enough to produce large canyon‐channel systems that can concentrate flows downslope [e.g., Kremer et al ., , ; Normandeau et al ., ]. Instead, the flows being triggered at the delta front remain largely unconfined.…”
Section: Discussionmentioning
confidence: 99%
“…Known turbidite thickness in East Lake (millimeter scale) and the runoff of the river which attains peaks of 1–2 m 3 /s during snowmelt (peak discharge) also suggest that the hyperpycnal flows are rather dilute. These low‐energy hyperpycnal flows are not erosive enough to produce large canyon‐channel systems that can concentrate flows downslope [e.g., Kremer et al ., , ; Normandeau et al ., ]. Instead, the flows being triggered at the delta front remain largely unconfined.…”
Section: Discussionmentioning
confidence: 99%
“…The various types of MTDs that were described in the sedimentary record of the distal basin of Lake Geneva significantly contributed to the sediment budget of the deep lake basin with volumes ranging from 22 Â 10 6 to 250 Â 10 6 m 3 (Kremer et al, 2015c). The mobilized volumes are in the same order of magnitude than similar events in the marine realm (Hampton et al, 1996;Talling, 2014).…”
Section: The Mass-transport Deposits Control On Sediment Dispersal Pamentioning
confidence: 93%
“…As an example, the Nice airport scarp failure in 1979 evolved into a hybrid flow that mobilized 8 Â 10 6 m 3 -similar to the volume displaced by the 1998e2000 CE MTD event -and triggered a tsunami wave 2e3 m height (Mulder et al, 1997). A simplified tsunami wave numerical model of Lake Geneva (Kremer et al, 2015c) has recently shown that mass movements involving sediment volumes of 10 6 e10 7 m 3 could lead to 1e3 m high waves, reaching the adjacent lakeshore in only a few minutes. In the present case, no significant sudden lake level change was recorded in Lake Geneva limnological stations between 1998 CEe2000, a priori indicating that the 1998e2000 CE event did not trigger a tsunami wave.…”
Section: Implications For Geohazard Assessmentsmentioning
confidence: 99%
“…At Hellsete, onshore landslide debris confining the delta plain, major irregular debris at the delta toe, and a distinct debris lobe laterally to the delta slope, also indicate a significant influence of landslide and avalanche activity. Deltaic protuberances and other special features associated with delta collapse have been reported from other fjord-type lakes (e.g., Hilbe & Anselmetti, 2014;Kremer et al, 2015). These authors have assigned such features to seismic events or overloading due to rock falls, respectively.…”
Section: The Shaping Of Fan Deltas and Bødalsdeltamentioning
confidence: 88%
“…This includes the information on depositional products as well as the behaviour and causal relationships between sedimentary processes. Such information is especially crucial for the understanding of hazardous events in the basins (e.g., Bøe et al, 2003;Longva et al, 2003;Blikra et al, 2006;L'Heureux et al, 2009L'Heureux et al, , 2012Ledoux et al, 2010;Hilbe et al, 2011Hilbe et al, , 2014Van Daele et al, 2013;Haeussler et al, 2014;Kremer et al, 2015;Wiemer et al, 2015). In Figure 1 this context, the linkage of offshore-onshore datasets is crucial as it provides clues to the many processes that occur in both environments (e.g., Bozzano et al, 2009;Couchon-Voyer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%